DIPG-39. NOVEL PROTEOMIC ANALYSIS REVEALS EPIGENETIC THERAPEUTIC TARGETS IN PEDIATRIC GLIOMA - Li, Daphne (Neuro Oncol, 2020)
INTRODUCTION: Diffuse midline glioma is a highly morbid pediatric cancer. Up to 80% harbor Histone H3K27M mutation, which alters Histone H3 post-translational modifications (PTMs) and genomic enrichment patterns, affecting chromatin structure and transcription. We previously identified tumorigenic patterns of H3K27Ac/bromodomain co-enrichment and pre-clinical efficacy of bromodomain inhibition (JQ1) in DMG. Here, we employ a novel proteomics approach developed at our institution to further elucidate the impact of H3K27M mutation on glioma epigenetic signatures and treatment response. METHODS: Epiproteomic analysis was performed on pediatric glioma cells (H3K27 WT n=2, H3K27M n=2) to characterize 95 distinct Histone H3 N-terminal tail modification states. Cells were treated with JQ1 or DMSO, and collected at 0h, 24h, 48h, Histones extracted from isolated nuclei and immunopurified, then analyzed by LC-MS/MS. Results were integrated with RNA-Seq and ChIP Seq (H3.3K27M, H3.3, H3K27Ac, H3K27me3, H3K4me1, H3K4me3) from the same cell lines. Pediatric glioma tissues (H3K27M WT n=3, H3K27M n= 9) were similarly analyzed to validate cell line results. RESULTS: Cell PTM profiles cluster by H3 mutation status on unsupervised analysis. Significant differential PTM abundance and genomic enrichment H3K27M, H3.3 WT, H3K27Me3 and H3K27Ac was observed between mutant and wild type cell lines with epigenetic-targeted therapy, correlating with cell transcriptomes. CONCLUSIONS: Histone H3 tail analysis reveals the effects of H3K27M mutation and bromodomain inhibition on the tumor epigenetic landscape, providing insight into mechanisms of tumorigenesis and therapy response. Further investigation of the utility of these signatures as biomarkers for diagnosis and monitoring treatment response are therefore underway.